Dust a Richard Jury mystery - Grimes, Martha (New York Viking, 2007)
Richard Jury investigates the death of a wealthy bachelor with a mysterious past who was last seen in a club named Dust.
Keywords: Jury, Richard (Fictitious character) -- Fiction; Police -- England -- Fiction; Mystery fiction